Quantitative analysis of nitrite in blood-red bird's nest by high-performance liquid chromatography - Ruengdit, Manowich; Chanacot, Nipaporn; Torateekorntawat, Warinkarn (Bulletin of Applied Sciences, 2022)
This research aims to study the nitrite testing in bird nest which was extracted by water and determined by high performance-liquid chromatography technique (HPLC). The suitable HPLC condition revealed with the use of C18 reverse phase as stationary phase and 0.01 M octylammonium orthophosphate 30% v/v in methanol (pH 7.0) as mobile phase at flow rate 0.8 mL/min. The photodiode-array detector at a wavelength of 210 nm was applied. According to method validation, the linearity ranged from 0.5-250 pg/mL and 0.9999 for correlation coefficient. The limit of detection (LOD) and the limit of quantitation (LOQ) were 0.12 and 0.15 mg/kg, respectively. The recoveries were 107.5% at 0.5 ug/mL, 106.6% at 125 ug/mL and 105.3% at 250 ug/mL. The relative standard deviations (RSD) were 1.61, 0.43 and 0.49 respectively as well as uncertainty value conformed to the acceptable criteria. Therefore, this method provides good accuracy and precision that can be used for nitrite determination in bird nest. The thirteen samples of bird nest from nine provinces in the central, eastern and southern regions of Thailand were investigated in order to confirm the method application. The result ranged from not detected to 1652.7 mg/kg.